2016
DOI: 10.1152/jn.00303.2015
|View full text |Cite
|
Sign up to set email alerts
|

Tactile texture signals in primate primary somatosensory cortex and their relation to subjective roughness intensity

Abstract: Bourgeon S, Dépeault A, Meftah EM, Chapman CE. Tactile texture signals in primate primary somatosensory cortex and their relation to subjective roughness intensity. J Neurophysiol 115: 1767-1785, 2016. First published February 10, 2016 doi:10.1152/jn.00303.2015.-This study investigated the hypothesis that a simple intensive code, based on mean firing rate, could explain the cortical representation of subjective roughness intensity and its invariance with scanning speed. We examined the sensitivity of neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 68 publications
5
15
0
Order By: Relevance
“…With this caveat, the responses of APC neurons to gratings and dot patterns have been shown to be modulated by the spatial period of the stimuli. However, a subset of these neurons seems to track the perceived roughness of such textures (25, 53), consistent with the hypothesis that they are causally implicated in texture perception. Furthermore, lesions of area 1 result in pronounced deficits in texture dis- crimination (296, 333, 334), so this area may be part of a pathway specialized for texture processing.…”
Section: Sensory Coding In Somatosensory Cortexsupporting
confidence: 80%
“…With this caveat, the responses of APC neurons to gratings and dot patterns have been shown to be modulated by the spatial period of the stimuli. However, a subset of these neurons seems to track the perceived roughness of such textures (25, 53), consistent with the hypothesis that they are causally implicated in texture perception. Furthermore, lesions of area 1 result in pronounced deficits in texture dis- crimination (296, 333, 334), so this area may be part of a pathway specialized for texture processing.…”
Section: Sensory Coding In Somatosensory Cortexsupporting
confidence: 80%
“…While we did observe significant differences in speed-sensitivity across different afferent classes (Delhaye et al, 2019), every submodality trended towards more speed-sensitivity than that was observed in cortex (RA: 29.3%±3.3% and PC: 35.0%±5.4%, p < 0.05, SA1: 23.8%±6.2%, p=0.18, see Supplementary Figure 2A -B). The speed-sensitivity of responses in area 3b trended towards smaller values than responses from areas 1 and 2 (area 3b: 12.9%±9.8% < area 1: 23.1%±7.5% at p<0.05 and area 2: 24.4%±24.9%, p=0.33, see Supplementary Figure 2A-B), consistent with previous reports (Bourgeon et al, 2016;Dépeault et al, 2013). Figure 1.…”
Section: Speed-dependence Of Firing Ratessupporting
confidence: 89%
“…As signals ascend the somatosensory hierarchy, the tuning of individual neurons becomes increasingly heterogeneous . We might thus expect subpopulations of cortical neurons to show specialization for speed or texture coding (Bourgeon et al, 2016;Dépeault et al, 2013). Indeed, we found a significant proportion of cortical cells exhibited speed ratios weaker than any observed in peripheral afferents ( Figure 1E) (12/49 with ratio < 0.12, p<0.05, permutation test, see Methods), an effect that was present in all three cortical areas (Supplementary Figure 2D).…”
Section: Speed-dependence Of Firing Ratesmentioning
confidence: 71%
See 1 more Smart Citation
“…However, it remains unknown whether this area is also critical for the conscious tactile perception of object properties such as textures. Previous electrophysiological studies involving monkeys have demonstrated that neurons in S1 are involved in the perception of texture (Bourgeon, Depeault, Meftah el, & Chapman, 2016;Chapman, Tremblay, Jiang, Belingard, & Meftah el, 2002;Sinclair & Burton, 1991) and vibrational frequency (Romo, Lemus, & de Lafuente, 2012). However, such studies have been unable to clarify the extent to which such activity is associated with conscious texture perception.…”
Section: Discussionmentioning
confidence: 98%